METHODICAL CLUSTER - AS AN INNOVATIVE MECHANISMS TO INCREASE THE EFFICIENCY OF HIGHER EDUCATION - Teshaboeva Feruza Raximovna, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article provides recommendations for the organization of methodological services based on innovative approaches that affect the quality of higher education. At the same time, the effectiveness of the methodological service depends on the quality of staff and the need to adapt the goals and objectives of the educational institution, based on the requirements of social order, to the qualification requirements of future professionals. In particular, the stages of the "Methodological Cluster" and the content of the work carried out in these stages are given.